2022
DOI: 10.3847/psj/ac7d5a
|View full text |Cite
|
Sign up to set email alerts
|

New Constraints on the Volatile Deposit in Mercury’s North Polar Crater, Prokofiev

Abstract: We present new high-resolution topographic, illumination, and thermal models of Mercury’s 112 km diameter north polar crater, Prokofiev. The new models confirm previous results that water ice is stable at the surface within the permanently shadowed regions (PSRs) of Prokofiev for geologic timescales. The largest radar-bright region in Prokofiev is confirmed to extend up to several kilometers past the boundary of its PSR, making it unique on Mercury for hosting a significant radar-bright area outside a PSR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Thicker low‐reflectance layers along polar deposit boundaries, leading to a decrease in relative water‐ice content, could be consistent with radar signatures being weaker along polar deposit margins (Meyer et al., 2021; Rivera‐Valentín et al., 2022). Furthermore, variations in lag deposit thickness may be supported by observations of the north polar Prokofiev crater, whose polar deposit appears to transition from a high‐reflectance exposed water‐ice deposit within its PSR to an insulated, still strongly radar‐bright deposit outside of its PSR in a boundary zone where water ice is stable in the upper meter (Barker et al., 2022; Deutsch et al., 2016; Rivera‐Valentín et al., 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Thicker low‐reflectance layers along polar deposit boundaries, leading to a decrease in relative water‐ice content, could be consistent with radar signatures being weaker along polar deposit margins (Meyer et al., 2021; Rivera‐Valentín et al., 2022). Furthermore, variations in lag deposit thickness may be supported by observations of the north polar Prokofiev crater, whose polar deposit appears to transition from a high‐reflectance exposed water‐ice deposit within its PSR to an insulated, still strongly radar‐bright deposit outside of its PSR in a boundary zone where water ice is stable in the upper meter (Barker et al., 2022; Deutsch et al., 2016; Rivera‐Valentín et al., 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Modeling surface illumination also constitutes the first step toward retrieving the thermal evolution at or near the surface. In turn, knowledge of near-surface temperature over time is key to determining the nature of radar-bright deposits observed at Mercury poles (Harmon et al 2011;Chabot et al 2018), as previously shown at Mercury's north pole (Paige et al 2013;Chabot et al 2018b;Hamill et al 2020;Barker et al 2022;Gläser 2022). For instance, an accurate modeling of near- surface maximum and average temperature is necessary to assess whether water ice (or other volatiles) can survive near the surface over geological timescales.…”
Section: Discussionmentioning
confidence: 95%
“…More accurate simulations, based on the complete MLA data set, were first published in Chabot et al (2018b), and more recently by Gläser (2022). Other studies (Deutsch et al 2016;Rubanenko et al 2018;Susorney et al 2021) have also focused on the north polar region leveraging the MLA elevation models (see, e.g., Zuber et al 2012;Hamill et al 2020;Barker et al 2022), in part because no reliable high-resolution elevation data for the southern polar region are available.…”
Section: Introductionmentioning
confidence: 99%
“…Although MDIS imaging of the surface within the PSR of Prokofiev was not calibrated to reflectance values, the images also revealed a brighter region in the same areas where the thermal models predict that ice can be thermally stable at the surface (Chabot et al 2014). Detailed higher spatial resolution modeling of Prokofiev concluded that while water ice is present at the surface, the surface reflectance was not consistent with pure ice (Barker et al 2022).…”
Section: Introductionmentioning
confidence: 96%
“…The Mercury Dual Imaging System (MDIS) captured multispectral images of Mercuryʼs surface, and the Mercury Laser Altimeter (MLA) measured the northern hemisphere topography (Solomon & Anderson 2018). These measurements enabled the derivation of maps of shadowed regions, which showed a considerable overlap with the radar-bright deposits near both poles (Deutsch et al 2016;Chabot et al 2018b;Barker et al 2022;Gläser & Oberst 2022;Bertone et al 2023). Modeling of the thermal conditions using the MLA-determined topography at Mer-curyʼs north polar region revealed that water ice was stable over geologic timescales within many of the permanently shadowed regions (PSRs; Paige et al 2013;Chabot et al 2018a).…”
Section: Introductionmentioning
confidence: 99%